Paternal and maternal prescription opioid use and misuse: General and specific risks for early adolescents' substance use. (April 2020) - Kerr, David C.R.; Tiberio, Stacey S.; Capaldi, Deborah M.; Owen, Lee D.
Highlights: Fathers' prescription opioid misuse was associated with children's substance use by age 14 years. Mothers' prescription opioid use but not misuse was correlated with child substance use. Risk from mothers' opioid use was not explained by mothers' more general behavioral risks. Risk transmission was stronger with higher father–child residential contact. Abstract: Background: Parent substance use is a risk factor early adolescents' substance use. Theoretical models of deviance and general substance use risk may not apply to risk-transmission pathways involving parents' prescription opioid misuse (POM) and child outcomes. Thus, we examined predictions of children's alcohol, tobacco, and marijuana (ATM) use in early adolescence, from parental POM, delinquency, depressive symptoms, and ATM use. Method: Children ( n = 216; 121 female) participated from early childhood to ages 11–12 or 13–14 years with their 111 fathers and 136 mothers. At all available waves, self-reports were collected on each parents' POM, ATM, prescription opioid use (POU), depressive symptoms, and delinquent behavior, and children's ATM use. Results: Poisson regressions were run separately by parent, controlled for child age and gender and paternal age at child's birth, and accounted for clustering of children in families. Child ATM use was predicted by paternal POM, but the effect was better explained by paternal ATM use, which was a stronger effect in families with higher father–child residential contact. In contrast and unexpectedly, mothers' POU but not POM predicted child ATM use, and the effect was not explained by the significant predictions from maternal ATM use and delinquency. Conclusion: Fathers' POM and mothers' POU predicted child ATM use by early adolescence. Findings generally were consistent with parent–child risk–transmission processes described for other substances. Resident fathers' substance use and multiple maternal risk factors are worthy foci for prevention of the intergenerational transmission of substance use.